The Influence of Parental Income and Independence on Student Learning Motivation - Firyal Nabila Afifah; Mirna Dewi Anggraini; Suparmi (Idarah (Jurnal Pendidikan dan Kependidikan), 2024)
This research aims to analyze the influence of parental income and learning independence on students' motivation to learn. The subjects of the study were 101 students in the 2nd and 4th semesters of the Bachelor's program in Educational Technology at Sebelas Maret University. Data were collected through questionnaires, and analysis was conducted using simple regression with SPSS 22.0. The results showed that: (1) there was no significant effect between parental income and learning motivation, with a t-value of -0.097 < t-table 1.66 and a significance level of 0.923 > 0.05; (2) there was a significant positive effect between learning independence and learning motivation, with a t-value of 14.403 > t-table 1.66 and a significance level of 0.000 < 0.05; (3) simultaneously, parental income and learning independence had a significant positive effect on learning motivation, indicated by an F-value of 103.035 > F-table 3.09 and significance <0.00 < 0.05. This study emphasizes the importance of learning independence in enhancing motivation regardless of parental income.